2018
DOI: 10.1111/jam.13912
|View full text |Cite
|
Sign up to set email alerts
|

Development and antimicrobial application of plantaricin BM-1 incorporating a PVDC film on fresh pork meat during cold storage

Abstract: The results of this study suggest a potential application of bacteriocin active film on meat preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Over the last five years, the use of enterocin AS-48 [47], bacteriocins-like substances [48] or bacteriocin-producing strains [49] with modified atmosphere packaging or high hydrostatic pressure has yielded improved results in the packaging of chilled food products. Furthermore, bacteriocin combination with other antimicrobials such as thymol [47,50], carvacrol [50], EDTA [51] or chitosan [17,52] have also improved their antibacterial action in food products such as meat and fish.…”
Section: Antimicrobial Substances Used In Food Packagingmentioning
confidence: 99%
“…Over the last five years, the use of enterocin AS-48 [47], bacteriocins-like substances [48] or bacteriocin-producing strains [49] with modified atmosphere packaging or high hydrostatic pressure has yielded improved results in the packaging of chilled food products. Furthermore, bacteriocin combination with other antimicrobials such as thymol [47,50], carvacrol [50], EDTA [51] or chitosan [17,52] have also improved their antibacterial action in food products such as meat and fish.…”
Section: Antimicrobial Substances Used In Food Packagingmentioning
confidence: 99%
“…After 7 days of storage, 100 μg/ml of Hispidalin lowered TVC by approx.1.40 Lg CFU/g, which was in consistent with other AMPs as previously reported. It have been reported that plantaricin BM‐1 incorporating a PVDC film significantly reduced TVC by approx.1.47 Lg CFU/g in fresh pork after 7 days of storage (Xie et al, 2018). Housefly peptide reduced TVC by approx.…”
Section: Dicussionmentioning
confidence: 99%
“…Genes encoding plantaricin are located both on a plasmid and in a chromosomal region. This information explains the diversity and characterization of plantaricin in Table 2. References Chikindas et al, 1993;Kaur and Kaur, 2015;Zacharof andLovitt, 2012 Bengtsson et al, 2020;Kristiansen et al, 2005;Oppegård et al, 2016;Xu et al, 2019Ahmad et al, 2017Collins et al, 2017;Diep et al, 2007Hata et al, 2010Perez et al, 2014;Todorov, 2009 Figure 1 Plantaricin biosynthesis gene cluster L. plantarum WCFS1; a -d. plnW, plnV, plnU, and plnT, integral membrane protein, respectively; e. plnS, two-peptide bacteriocin; f. plnH, bacteriocin ABC transporter, accessory factor plnH; g. plnG, bacteriocin ABC-transporter, ATP-binding and permease protein; h -i. plnE and plnF, two-peptide bacteriocin; j. plnD, response regulator, repressor; k. plnC, response regulator, activator; l. plnB, histidine protein kinase, sensor protein; m. plnA, precursor peptide, induction factor; n. plnQ, plantaricin biosynthesis protein; o. plnP, bacteriocin immunity protein; p. plnO, plantaricin biosynthesis protein; q. plnN, bacteriocin precursor peptide; r. plnM, bacteriocin immunity protein; s -t. plnJ and plnK, two-peptide bacteriocin plantaricin JK; u. plnL, bacteriocin immunity protein Many other plantaricins have been reported, such as plantaricin 149 (Kumagai et al, 2019), plantaricin JY22 (Lv et al, 2018), plantaricin ZJ5 (Song et al, 2014), plantaricin LPL-1 (Wang et al, 2018), plantaricin NC8 (Jiang et al, 2018), and plantaricin BM-1 (Xie et al, 2018). Their different c...…”
Section: Characterization and Heterogeneity Of Plantaricinmentioning
confidence: 99%
“…Plantaricin was developed as an active antibacterial packaging film by coating a polyethylene terephthalate/polyvinylidene chloride/retort casting polypropylene multilayer film with plantaricin BM-1 and chitosan, for chilled meat preservation (Yang et al, 2019). This was reported to prolong the shelf life of pork during cold storage (Xie et al, 2018). The active plantaricin film significantly decreased the surface population of L. monocytogenes, compared to the control (Yang et al, 2019), and is reported to cause direct cell disruption (Ercolini et al, 2006).…”
Section: Antibacterial Packagingmentioning
confidence: 99%
See 1 more Smart Citation